Proprioception in musculoskeletal rehabilitation. Part 1: Basic science and principles of assessment and clinical interventions. Issue 3 (June 2015) - Röijezon, Ulrik; Clark, Nicholas C.; Treleaven, Julia
Abstract Introduction Impaired proprioception has been reported as a feature in a number of musculoskeletal disorders of various body parts, from the cervical spine to the ankle. Proprioception deficits can occur as a result of traumatic damage, e.g., to ligaments and muscles, but can also occur in association with painful disorders of a gradual-onset nature. Muscle fatigue can also adversely affect proprioception and this has implications for both symptomatic and asymptomatic individuals. Due to the importance of proprioception for sensorimotor control, specific methods for assessment and training of proprioception have been developed for both the spine and the extremities. Purpose The aim of this first part of a two part series on proprioception in musculoskeletal rehabilitation is to present a theory based overview of the role of proprioception in sensorimotor control, assessment, causes and findings of altered proprioception in musculoskeletal disorders and general principles of interventions targeting proprioception. Implications An understanding of the basic science of proprioception, consequences of disturbances and theories behind assessment and interventions is vital for the clinical management of musculoskeletal disorders. Part one of this series supplies a theoretical base for part two which is more practically and clinically orientated, covering specific examples of methods for clinical assessment and interventions to improve proprioception in the spine and the extremities.